AB1013 Prediction of bone mineral density changes in patients with rheumatoid arthritis. (12th June 2018) - Tomizawa, T.; Ito, H.; Furu, M.; Hashimoto, M.; Tanaka, M.; Mimori, T.; Matsuda, S.
Abstract : Background: Osteoporosis and its related fractures is one of the most dominant, troublesome complications in rheumatoid arthritis (RA). Newly-introduced drugs such as methotrexate and biological and targeted synthetic disease modifying anti-rheumatic drugs have decreased disease activity drastically, but the improvement of osteoporosis remains to be investigated. Objectives: To find useful factors for bone mineral density (BMD) management of RA patients under the current treatment. Methods: We consecutively recruited 370 RA patients treated at Kyoto University Hospital in 2012. We prospectively collected the BMD values of the lumbar spine and the distal forearm measured by dual-energy X-ray absorptiometry (DXA), blood sampling test, urinalysis including bone metabolic biomarkers and clinical parameters of the RA patients in 2012 and 2014. Multivariate regression analysis was performed after adjustment by age, sex, body mass index (BMI), steroid use, anti-osteoporosis medication. We set the annualised BMD change as an outcome variable and allotted the other parameters as explanatory variables by a stepwise procedure. Results: The average values (minimum-maximum value) of age and BMI were 63.3 (32–85) years and 22.1 (12.3–30.0), respectively. Female patients and steroid users accounted for 91.1%, and 41.0%, respectively. Coincidentally, anti-osteoporosis drug-user also reached 41.0%. User of biological accounted for 30.8%. The averages of disease activity score (DAS) 28-erythrocyte sedimentation rate, Health Assessment Questionnaire was 2.6 (0.1–5.9) and 0.8 (0–2.9), respectively. The average of total Sharp score was 122.6 (0–443). Laboratory data showed serum tartrate-resistant acid phosphatase (TRACP)−5b, serum homocysteine, serum undercarboxylated osteocalcin, bone specific alkaline phosphatase, and urinary pentosidine were 320.0 (68–877) mU/dl, 9.7 (3.2–28) nmol/ml, 4.8 (0–23) ng/mL, 15.6 (5.8–43.6) µg/L, and 50.0 (11.5–561) pg/ml, respectively. Next, we describe by the result of multiple regression analysis. The levels of serum homocysteine (β=−0.19; 95%CI: 0.24 to 1.75; p=0.01) and anti-osteoporosis drug (β=−0.19; 95%CI; −0.26 to −0.04; p=0.009) were consistently significant predictive variables of annualised BMD change of the lumbar-spine. On the other hand, serum TRACP-5b (β=−0.28; 95%CI; −0.005 to −0.001; p=0.002) was significant predictive one for the distal forearm. Conclusions: Anti-osteoporosis medication may be particularly important for lumbar spine BMD for RA patients, regardless of steroid-use. Specific biomarkers would be useful such as homocysteine as lumbar spine BMD and TRACP-5b as the forearm BMD. These findings would be helpful for osteoporosis management in RA patients. Reference: [1] Hippisley-Cox J, Coupland C. Derivation and validation of updated QFracture algorithm to predict risk of osteoporotic fracture in primary care in the United Kingdom: prospective open cohort study. BMJ2012;344:e3427 Acknowledgements: K. Nishitani, K. Murata, M. Azukizawa, K. Murakami, S. Nakabo, T. Nakajima Disclosure of Interest: None declared